Entrepreneurship the Disney Way - Goldsby, Michael; Mathews, Rob (Ascent Audio, 2019)
This book focuses on the business story of Walt Disney and the company he built. Combining a unique blend of entrepreneurship, creativity, innovation, and a relentless drive to bring out the best in his teams, Walt Disney created one of the most successful ventures in business history. Outlining the specific processes of the company, Goldsby and Mathews provide the listener with the tools they need to embrace their own entrepreneurial leadership style, to lead effectively, to be more innovative, and to build a successful organization. Through the lens of Disney, the listener learns the fundamentals of entrepreneurship, innovation, and leadership. Beginning with a general introduction to the concepts relevant to the entrepreneurial organization today, the book examines how Disney built his empire and how the company remains an industry leader. The book also provides the opportunity to take the Entrepreneurial Leadership Instrument, which measures one's style in leading entrepreneurial ventures. Entrepreneurship the Disney Way brings entrepreneurship, innovation, and leadership to life through the compelling story of one of the most recognizable businessmen and companies of our time.